Community theatre as a tool for social change: the case Amakhosi productions- “don’t –ungaqali” and “stop - Tshuma, Sehlisiwe (Midlands State University, 2017)
The study examines the use of community theatre as an effective tool for social change compared to other forms of theatre. It focuses on the influence of theatre to the audiences. The study made use of two theatrical plays produced by Amakhosi Theatre as reference in evaluating the ability of community theatre in changing people‟s mindsets, attitudes, behaviors and perceptions for the improvement of Zimbabwean communities. Thus the research purposes was to explore how community theatre builds the capacity of an individual and community members with the potential to empower, energize, commission, encourage and strengthen. Qualitative methods of collecting information were used; these include archival analysis, case studies, interviews and questionnaires. Qualitative content analysis and discourse analysis were used to analyze the gathered information. The research established that community theatre is one mode of communication that brings communities together for a good common cause. The fact that it allows audience participation breaking the glass ceiling that separate actors and audiences creating spectators makes it effective as audiences participate thus creating one force that transforms communities. The research sought to assess the change brought about by community theatre in communities and from the gathered information community theatre contribute to the modeling and nurturing of characters for the improvement of communities.